The Relevance of the Character of Khulafaurrasisyidin to the Education of Tengka Madura - Intan Dwi Permatasari; Maimun, Maimun; Ach Syafiq Fahmi (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to correlate the character of Khulfaurrasyidin with the Tengka education in Madura. This research uses the Library Research research method, namely a research method in which information is obtained by referring to books, journals, articles, newspapers, history books and so on. The results of this research state that firstly, the caliph Abu Bakar and his correlation to Tengka's education is his honest character in accordance with the caliph's nickname, namely "As-Shiddiq", secondly, the caliph Umar bin Khattab and his correlation to Tengka's education is his tough and firm character in fighting for the truth. in Islam, the three caliphs Ustman bin Affan and the correlation with Tengka's education are zun-nurain (two lights) because he married 2 daughters of the Prophet, the fourth caliph Ali bin Abi Talib and the correlation with Tengka's education is Babul 'Ilm (door of knowledge) which is related with Tengka education, Madurese people always prioritize science in all aspects.